The new clash of generation - Dores, A. P.; Sousa e Silva, M. (Revista Estudos Institucionais, 2020)
Unlike in the sixties, today's clash of generations is not about creating (post-)materialistic values. It is about human species survival. The fear of decay (of the Empire through war) and the hope of revolution ( coming back a new to a starting configuration) are similar. Social State´s financial sustainability or the new generation of energy sources are partial problems. How to have justice for all, including the environment?, that´s a global problem. The main and also repressed question is about how climate change will impose new ways of living on us all.Political and cognitive alienation from the main human problems is pushing emotional responses in different directions. Alienation closes political systems from population and from it springs populist irrationality in politics, racist and sexist scapegoating, consumers street uprisings, etc. Considering the regulatory function of the law over technology, social exclusion, war, one can assess the way modern law focuses on intergeneration relationships and how a healthy environment has been dismissed as a human right. For this propose one will consider the ongoing legal attempts to criminalize ecocide.